2019
DOI: 10.3354/dao03368
|View full text |Cite
|
Sign up to set email alerts
|

Method for serial passage of infectious hematopoietic necrosis virus (IHNV) in rainbow trout

Abstract: Transmission is a fundamental component of pathogen fitness. A better understanding of pathogen transmission can greatly improve disease management. In particular, controlled studies of multiple rounds of natural transmission (i.e. serial passage) can provide powerful epidemiological and evolutionary inferences. However, such studies are possible in only a few systems because of the challenges in successfully initiating and maintaining transmission in the laboratory. Here we developed an efficient and reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…There was no evidence that reductions in recovery rate are outweighed by truncation of host lifespan at the virulence levels studied here. This is likely because shedding of the virus is very acute and mostly occurs before mortality begins [82][83][84].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no evidence that reductions in recovery rate are outweighed by truncation of host lifespan at the virulence levels studied here. This is likely because shedding of the virus is very acute and mostly occurs before mortality begins [82][83][84].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The raceway volume (183,219 L), and water exchange rate (72 flushes/day), were chosen to represent conditions on a typical North American trout farm [134][135][136][137]. Transmission is also assumed to be driven by fish contact with virus particles in the water [69][70][71][72][73][74][75][82][83][84]. Recovery rate equaled 1/mean duration of shedding (last day-first day + 1) for fish infected with each IHNV genotype; calculated using Kaplan-Meier analysis (survfit) on experiment 1 data.…”
Section: Transmission Model Of Ihnv Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, vaccination reduced pathogen fitness by an order of magnitude or less (i.e., resulted in reduction in total shedding). If viral shedding is correlated with transmission as other studies have suggested (Wargo and Kurath 2012;Doumayrou et al 2019), this would imply that vaccinated hosts are still able to transmit the virus, despite experiencing little clinical disease. Epidemiologically, the ability of vaccinated individuals to transmit the disease could greatly hinder management and eradication of disease, particularly if there is transmission between vaccinated and unvaccinated fish (e.g., between wild and cultured populations; Troyer and Kurath 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Host-to-host transmission through the entire infectious period is difficult to measure for IHNV and many other pathogens. However, previous studies have shown that IHNV transmission is correlated with the amount of virus shed from the host into the water (Doumayrou et al 2019). Here, we used viral shedding that was quantified at numerous time points throughout the infection as an estimate of transmission.…”
mentioning
confidence: 99%